The Skilled Colombian Immigrant Population Residing in the United States - Bermúdez Rico, Rosa Emilia (Sociedad y Economía, 2015)
In this article, the highly qualified Colombian population resident in the United States is characterized. Based on the information available at The American Community Survey, it presents a detailed socio-demographic description and identifies trends that characterize this population between 2000-2011. The analysis shows the dynamism achieved by this migrational flux; indicates a greater and more qualified participation of women and discusses the place taken by it in the South-North skilled mobility.